Tapping the potential for energy storage in community energy initiatives - Kiamba, Lorna; Rodrigues, Lucélia Taranto; Marsh, Julian (2017)
Driven by environmental concerns resulting from global warming, interest in renewable energy has grown in recent times. Similarly, improved efficiency and reliability in energy technologies have played a significant role in facilitating their adaptation at various scales. Of these technologies, energy storage has been suggested to have potentially far-reaching benefits including: more effective utilisation of renewable sources, better integration into smart energy systems and the improvement of grid reliability. In a community energy setting, energy storage can be used to stow away energy generated during low demand periods. This energy can then be accessed by community members at a lower cost during periods when there is higher demand and when energy is more likely to be expensive to buy. In this paper, the authors review the potential benefits of integrating energy storage into community energy initiatives based on the experiences of a community energy company set up in the Meadows in Nottingham, UK. In addition, the barriers they experienced when trying to maximise on these benefits including inefficient government policy and regulations, high capital cost and a lack of replicable business models, are highlighted. The results from t this case study review indicate that the introduction of energy storage can facilitate the future-proofing of community energy infrastructure with increased community and grid efficiencies as well as improve community resilience to changes in energy provision, particularly with regard to finances and infrastructure.